Penyuluhan Pencegahan Stunting Berbasis Digital Bagi Masyarakat Desa Mekarjaya Kecamatan Pacet Kabupaten Bandung - Amaliyah, Ani; Husni, Majmu'atil; Zakiyyah, Rosyidah; Azhari, Nyimas Ayu; Kusmiati; Nurlaela, Tutun; Nailassana, Syaila; Fauziah, Tasya Ramadhani; Aisy, Salsabila Radhatul; Lukman, Frida Febrandira; Malik, Muhammad Ridwan Abdul (Politeknik Piksi Ganesha Indonesia, 2024)
Abstract: Mekarjaya Village is included in the Pacet District of Bandung Regency with an area of 877.807 hectares. With a population of 8,491 people, consisting of 4,427 men and 4,064 women. Stunting is a chronic nutritional problem caused by a lack of nutritional intake over a long period of time, resulting in disruption of growth in children. Stunting is also one of the causes of children's stunted height, making them lower than other children their age. Likewise, stunting cases that occur in Bandung Regency, there are 21,018 stunted toddlers. So that community service activities are carried out by providing stunting prevention counseling. The solution to the problem is to provide stunting prevention counseling to the mekarjaya village community by KKN-T 12 UNINUS by providing information, insights and knowledge related to stunting prevention through counseling. The method of implementing the service was carried out using the needs analysis method. The results obtained are that the people of Mekarjaya village get an understanding of the concept of nutrition, routine checks for pregnant women, the importance of breastfeeding, and the level of hygiene.